The Contextual Ijtihâd of Umar ibn Khattâb: Between Legal Reform and Local Wisdom in Early Islamic Society - Amir Sahidin; Mohammad Muslih; Setiawan bin Lahuri; Zahrul Fata; Zahratur Rofiqah Binte Mochamad Sandisi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This article aims to situate Umar ibn al-Khattâb’s ijtihâd within the tension between the spirit of legal reform and loyalty to normative texts in the development of Islamic law following the death of the Prophet Muhammad. Various issues emerged after the death of the Prophet Muhammad that had never occurred during his lifetime. This situation prompted the Companions to exercise ijtihâd in response to the challenges of their time. In this context, Umar ibn al-Khattâb stands out as a prominent figure who introduced a number of legal decisions that appeared to diverge from practices established during the Prophet’s era. His ijtihâd included the suspension of the amputation penalty for theft, the annulment of hadd punishment for adultery, the decision not to distribute war booty among Muslim soldiers, and the discontinuation of zakât allocation to new converts (mu’allaf). Some scholars praise Umar’s sharp legal insight as being in harmony with the maqâshid al-syarî‘ah (the higher objectives of Islamic law), while others regard it as an early form of legal liberalization or even a deconstruction of the Islamic legal system. Employing a qualitative, library-based method with a descriptive analytical approach, this study finds that Umar’s ijtihâd did not abrogate fixed legal rulings in Islam but rather reflected a contextual sensitivity to socio-political realities that could hinder the just implementation of law. In conclusion, Umar’s ijtihâd represents a hermeneutical approach that balances textual fidelity with contextual awareness. The contribution of this study lies in emphasizing that Umar’s contextual approach offers a paradigmatic model for understanding the dynamics of contemporary Islamic law while remaining grounded in the principles of maqâshid al-syarî‘ah. Artikel ini bertujuan menempatkan ijtihâd Umar ibn al-Khattâb dalam ketegangan antara semangat reformasi hukum dan loyalitas terhadap teks-teks normatif dalam perkembangan hukum Islam pasca wafatnya Nabi Muhammad. Berbagai persoalan muncul setelah wafatnya Nabi Muhammad yang tidak pernah terjadi pada masa hidup beliau. Kondisi tersebut mendorong para sahabat untuk melakukan ijtihâd guna menjawab tantangan zaman. Dalam konteks ini, Umar bin Khattab tampil sebagai sosok yang menonjol dengan menetapkan sejumlah keputusan hukum yang tampak berbeda dari praktik pada masa Nabi. Ijtihâd tersebut antara lain berupa menggugurkan hukuman potong tangan bagi pencuri, menggugurkan hukuman hadd bagi pezina, tidak membagi harta rampasan perang kepada tentara Muslim, serta menghentikan pemberian zakat bagi mu’allaf. Sebagian ulama memuji ketajaman visi hukum Umar yang dinilai selaras dengan maqâshid al-syarî‘ah, sementara sebagian lain menilainya sebagai bentuk liberalisasi atau dekonstruksi terhadap sistem hukum Islam. Melalui metode kualitatif berbasis kajian pustaka dan pendekatan deskriptif-analitis, penelitian ini menemukan bahwa ijtihâd Umar tidak membatalkan hukum-hukum tetap dalam Islam, melainkan menunjukkan sensitivitas terhadap konteks sosial-politik yang dapat menghalangi penerapan hukum secara adil. Kesimpulannya, ijtihâd Umar merepresentasikan pendekatan hermeneutik yang seimbang antara kepatuhan terhadap teks dan kesadaran terhadap konteks. Kontribusi penelitian ini terletak pada penegasan bahwa pendekatan kontekstual Umar dapat menjadi model paradigmatik dalam memahami dinamika hukum Islam kontemporer yang tetap berlandaskan pada maqâshid al-syarî‘ah.